Francis B. Nyamnjoh's Intimate Strangers: Mapping "Fragmegration" in Botswanan Urban Centres (Global Journal of Human-Social Science, 2021)
This paper draws on Francis Nyamnjoh's Intimate Strangers to argue that Africa's uneven development has created growing gaps within/among African urban centers and countries, thereby engendering an African "fragmegration." That novel attests that Africans' mobility to African urban centres and countries with greener pastures such as Botswana is characterized by multiple layered identity (de/re)constructions based on integration-fragmentation and globalization-localization. Drawing on Botswanans' idea of "Makwerekweres" the paper argues for the promotion of difference and diversity. It further asserts that the nuances that Nyamnjoh's fiction brings to mobility, belonging, and globalization adumbrate socio-economic and politico-cultural interconnections and interdependencies. Reading Nyamnjoh's novel through the fragmegration lens asseverates his belief in nimble-footedness and flexibility in belonging. It is also a perspective that foregrounds the author's informative concepts of incompleteness and conviviality and thus the importance of reciprocal acknowledgement of the Other in her/his otherness among Africans, and between Africans and the West or the rest.
Keywords: fragmegration; locals; globals; cynics; illegals; passives; incompleteness